The Dimension of Public Administration in Central and Eastern European Countries in the Current Financial Crisis - Mihaela ONOFREI; Dan LUPU (Transylvanian Review of Administrative Sciences, 2010)
The article analyzes from a comparative perspective the main characteristics of the public function in countries from Central and Eastern Europe. Faced with financial crisis, the governments start taking measures regarding the public administration. The article analyzes the evolution of public administration in Romania between 1990 and 2009; the impact of financial crisis on it; and finally yet importantly, through an econometric model, it determines the relationship among the main factors of influence, GDP, public expenditure and the number of civil servants.